2009
DOI: 10.1111/j.1745-4549.2008.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Marine Fish Drying Using Solar Tunnel Dryer

Abstract: Studies were conducted to optimize fish‐drying process in a Hohenheim‐type solar tunnel dryer to produce safe and high quality dried fish products. Five commercially important tropical marine fish species in the Bay of Bengal such as silver jew fish, Bombay duck, big‐eye tuna, Chinese pomfret and ribbon fish were used and drying was performed at 45 to 50 and 50 to 55C temperature ranges. Moisture content of the fish samples reached 16% after 36 and 32 h of drying at temperature ranges of 45 to 50 and 50 to 55C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 17 publications
3
31
1
2
Order By: Relevance
“…It has been investigated that the initial pH of Pangasius sutchi was around 7.0 which gradually reduced to 5.98 during 14 th days of ice storage period and then increased [13]. Reza [19] also observed that, for different fish species such as Silver jewfish, Bombay duck, Bigeye tuna, Chinese pomfret and ribbon fish the pH gradually increased with the lapse of storage period, and at the end of 13 days of storage the pH increased up to 7.98 and it ranged within 7.2-7.98.Our results were very much similar with the result of Reza [22]. The initial low pH was because of formation of lactic acid during anaerobic glycolysis in fish muscle might be after the death.…”
Section: Changes In Ph Under Various Storage Conditionssupporting
confidence: 85%
“…It has been investigated that the initial pH of Pangasius sutchi was around 7.0 which gradually reduced to 5.98 during 14 th days of ice storage period and then increased [13]. Reza [19] also observed that, for different fish species such as Silver jewfish, Bombay duck, Bigeye tuna, Chinese pomfret and ribbon fish the pH gradually increased with the lapse of storage period, and at the end of 13 days of storage the pH increased up to 7.98 and it ranged within 7.2-7.98.Our results were very much similar with the result of Reza [22]. The initial low pH was because of formation of lactic acid during anaerobic glycolysis in fish muscle might be after the death.…”
Section: Changes In Ph Under Various Storage Conditionssupporting
confidence: 85%
“…It has been reported that the acceptable limit of total plate count for fresh fish is 7 log CFU/g [23]. The APC of some marine dried fish range between 3.27 and 4.49 log CFU/g [24]. Mansur et al [25] reported that the total bacterial count of some sun-dried fishes range between 1.84 and 5.3 log CFU/g.…”
Section: Discussionmentioning
confidence: 99%
“…Reza et al [34] observed that the total TVB-N content were 5.3 to 19.0 mg/100 g in traditionally sun dried ribbon fish. According to Connell [26], the upper limit of TVB-N is 30 mg/100 g, which certify the acceptable level for fin fish dried products.…”
Section: Discussionmentioning
confidence: 99%